Application of Numbered Heads Together (NHT) Type Cooperative Learning as an Increase in Understanding of the Concept of Water Cycle In Elementary School Science Subjects - Deden Dicky Dermawan (Zona Education Indonesia, 2023)
Natural Science is one of the main subjects at the elementary school level, which discusses knowledge about the natural surroundings and is closely related to everyday life. This study aims to improve understanding of the concept of the water cycle in science subjects elementary school students using the Numbered Heads Together (NHT) model. This study used a qualitative approach and the data analysis process emphasized the conclusion of comparative literature reviews from several scientific journals. The results show that using the Numbered Heads Together (NHT) model can improve understanding of the concept of the water cycle, can have a positive impact on learning, make students interested and enthusiastic in learning, all students become more active and ready to take part in learning, be responsible for work. groups, students become confident, develop student skills, and the learning process becomes more fun and less boring. Thus it can be concluded that the Numbered Heads Together (NHT) model can be used as a solution to improve understanding of the concept of the water cycle in elementary school science subjects